Interprofessional Education Perception among Faculty in Health Allied Professions in the Philippines: A Preliminary Study - Tuppal, Cyruz P.; Roa, Mary Nellie T.; Sison, Dennis C.; Frani, Jeeno Jay F.; Alarca, Cerina Joy M.; M. Dispolo, Marvin; E. Santero, Cristina; B. Verzosa, Ronald; S. Tu, Israel; S. Tu, Christian; J. Dupaya, Marinette; S. Perea, Godofredo; M. Francisco, Evangeline; B. Pacete, Shirley; S. Kalinawan, Sue; Buenaobra, Tita B.; Fille, Joselito O. (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Interprofessional education (IPE) has been recognized globally as critical for preparing health professionals to deliver collaborative and patient-centered care. In the Philippines, however, IPE remains in its early stages of development, with limited standardization across institutions and scarce research focused on faculty perceptions. Faculty play a vital role in implementing and sustaining IPE initiatives, making their perspectives essential to understanding the current landscape and barriers to IPE integration.Purpose: This study aimed to assess the perceptions of IPE among faculty members teaching in allied health programs in the Philippines and to identify factors influencing their attitudes toward interprofessional collaboration.Methods: A descriptive cross-sectional design was employed, surveying 328 faculty members from accredited Philippine institutions through a self-administered online questionnaire. Participants were selected using convenience sampling. The Interdisciplinary Education Perception Scale (IEPS) was used to measure perceptions, with excellent internal reliability (Cronbach’s α=0.984). Statistical analyses, including independent t-tests and one-way ANOVA, were conducted using SPSS version 27 after checking for normality (Shapiro-Wilk test) and homogeneity of variance (Levene’s test).Results: Faculty members demonstrated generally positive perceptions of IPE, particularly in valuing collaboration and recognizing the need for cooperation. No significant differences were found in overall perception scores based on age, gender, region, or years of teaching experience in the academe and years of clinical or professional practice in their respective health fields. However, statistically significant differences were observed across programs for perceived need for cooperation (p=0.000) and perception of actual cooperation (p=0.001), indicating a gap between intent and practice.Conclusion: While allied health faculty in the Philippines express supportive attitudes toward IPE, actual interprofessional collaboration remains limited. These findings highlight the need for faculty development initiatives, institution-wide policy frameworks, and longitudinal research to bridge the gap between perception and practice. Strengthening IPE implementation will be crucial to preparing future healthcare professionals for collaborative roles in improving patient outcomes.